Enchancement of nitrosoguanidine mutagenesis by chloramphenicol in Escherichia coli K-12. - Sklar, R (1978)
N-methyl-N'-nitro-N-nitrosoguanidine-induced mutagenesis in E. coli K-12 can be enchanced up to 50-fold by the addition of chloramphenicol with minimal effect on survival. Chloramphenicol does not produce the expected proportionate increase in closely linked double mutations.